A photocatalytic chip inspired from the photovoltaics of polymer-immobilized surfaces: self-assembly and other factors. Issue 96 (18th November 2021) - Ramar, Periyamuthu; Aishwarya, B. V.; Samanta, Debasis
Abstract : A "photovoltaic chip" can also be used as an efficient reusable "photocatalytic chip" when self-assembled in a particular fashion at a specific concentration ratio of the active materials. Abstract : Polymers and carbon nanomaterials for bulk heterojunction photovoltaic devices have been used to develop an efficient reusable photocatalytic chip. Interestingly, it is highly effective when the materials are self-assembled in a particular pattern at a particular concentration ratio (Movies in the ESI).